2022
DOI: 10.1002/cpt.2649
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetic Models for Direct Oral Anticoagulants: A Systematic Review and Clinical Appraisal Using Exposure Simulation

Abstract: Available data have shown an association between direct oral anticoagulant (DOAC) plasma concentration and clinical, particularly bleeding, events. Factors that may influence DOAC plasma concentration are therefore the focus of particular attention. Population pharmacokinetic (PopPK) analyses can help in identifying such factors while providing predictive models. The main aim of the present study was to identify all the PopPK models to date for the four most frequently used DOACs (dabigatran, apixaban, rivarox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…The population approach is widely used to identify the pathophysiological factors that cause changes in the dose–exposure–response relationship and, accordingly, if dose adjustment is required. Terrier et al [ 14 ] reviewed the effect of covariates on exposure to rivaroxaban [ 14 ], but they did not assess the difference in PK/PD among various ethnicities. Moreover, several population PK and PK/PD studies in Asians were reported to identify significant covariates based on CL in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…The population approach is widely used to identify the pathophysiological factors that cause changes in the dose–exposure–response relationship and, accordingly, if dose adjustment is required. Terrier et al [ 14 ] reviewed the effect of covariates on exposure to rivaroxaban [ 14 ], but they did not assess the difference in PK/PD among various ethnicities. Moreover, several population PK and PK/PD studies in Asians were reported to identify significant covariates based on CL in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Of all the patientspecific factors known to influence DOAC concentrations, clearance, and efficacy and safety, kidney function demonstrates the most impact for the individual patient and the population of DOAC users. 67,68…”
Section: The Role Of Kidney Functionmentioning
confidence: 99%
“…This analysis demonstrated a lower efficacy for dabigatran and warfarin in patients with kidney impairment and a lower safety for all OACs. Of all the patient‐specific factors known to influence DOAC concentrations, clearance, and efficacy and safety, kidney function demonstrates the most impact for the individual patient and the population of DOAC users 67,68 …”
Section: The Role Of Kidney Functionmentioning
confidence: 99%
“…A dose‐modification strategy based on advanced age, low body weight, and reduced renal function was designed to minimize the potential for higher exposure in populations at inherently higher bleeding risk 8,9 . Although the results of clinical studies have indicated that each factor individually has limited effect on apixaban exposure, the combinations of two or more intrinsic factors may increase apixaban exposure to a much greater extent 10–13 . In addition, when apixaban is used in real‐world conditions and in populations outside the rigorous setting of clinical trials, a larger interpatient variability in plasma concentrations is expected with growing evidence correlating higher apixaban exposures and hemorrhages 14–18 .…”
Section: Introductionmentioning
confidence: 99%